A new cobia (Teleostei, Rachycentridae) species from the Miocene St. Marys Formation along Calvert Cliffs, Maryland, USA. (May 2021) - Godfrey, Stephen J.; Carnevale, Giorgio
Abstract: The highly fossiliferous St. Marys Formation is exposed along Calvert Cliffs, Maryland, and comprises one of the best available records of late Miocene life in the northeastern United States. Rachycentron stremphaencus new species, a cobia from the late Miocene (Tortonian) of the St. Marys Formation is described herein on the basis of a single three-dimensional neurocranium. This fossil represents the earliest known occurrence of neurocranial remains of the genus Rachycentron in the record. Rachycentron stremphaencus differs from Rachycentron canadum (Linnaeus, 1766 ) in many ways. The most obvious include a different ornamentation of the outer surface of the cranial bones; a notably pronounced lateral ridge resulting in a considerable gradient from the dorsal-medial exposure of the frontal to its lateralmost supraorbital margin; the size, shape, and position of the sphenotic that is located in the posterior half of the neurocranium and its lateralmost edge being adjacent to the anteriormost extent of the wedge-shaped trough in the dorsal surface of the skull formed by the lateral and medial ridges; the two contralateral medial ridges forming a proportionately much wider trough on either side of the supraoccipital; the epioccipitals not reaching the rear edge of the neurocranium; and the lack of a conspicuous posterolateral prong of the intercalar. UUID: http://zoobank.org/c8523bb4-2de2-4318-9a37-027f463a0441